2 - Corruption and Human Rights: Positioning Judicial Activism as an Anticorruption Strategy in Kenya - Otieno, Ngira David (Africa Development, 2024)
This article locates the conceptual foundations of corruption and human rights by examining the normative and definitional challenges of these terms. By focusing on socioeconomic rights and the principle of equality in access to public services, the paper demonstrates the implications of corruption for the realisation of human rights. It then examines how the thin and thick conceptions of the rule of law interact with corruption. The article further explores legal corruption and the mechanisms by which graft corrupts the law-making process and compromises the rule of law. At the same time, the paper studies the role of judicial activism in fighting institutionalised and legal corruption in Kenya. In conclusion, it maintains that public interest and human rights considerations should be central to the law-making and interpretation processes. To effectively deal with corruption, activist judges should pursue the ends of justice rather than the law in the case of conflict between the two.